ANALISIS UPACARA ADAT PERKAWINAN TANIMBAR SEBAGAI ATRAKSI WISATA BUDAYA DI KABUPATEN MALUKU BARAT - Bet El Lagarense; Marthen Tombeng; Gerry Kadamehang; Mateus Londar (Jurnal Ilmu Pariwisata, 2023)
Traditional ceremonies are a cultural element that is internalized from time to time, which regulates and strengthens a very essential relationship between people of different types, which contains very broad and recognized values and norms, regulates and directs the behavior of each individual in a society. The form and value of culture shows that humans are the creators of culture. In other words, culture is the whole system of ideas, actions, and human creations to fulfill their lives. The method used in this research is qualitative. Sampling of data sources was carried out using purposive data based on observation, interviews, and documentation studies in reasonable and friendly situations without any influence or engineering. The results of the study show that traditional wedding in Tanimbar is a tourism asset that has two models of rites or ceremonies that are different from one another. The first model is the batnduwe/batnduan wedding and the batwalyete wedding. Efforts to preserve the traditional Tanimbar wedding ceremony as a cultural tourism attraction in West Southeast Maluku district is an opportunity to develop regional tourism.